Stress-Linked Tension Type Headache and Uncontrolled Diabetes: A Family Medicine Approach - Firmaniyah, Ulfa; Dasa Novita, Khuznita; Hevy Purwaningtyas, Nuretha (Jurnal Ilmu Kedokteran Keluarga, 2026)
xx